Multifaceted needs of individuals living with peripheral arterial disease: A qualitative study. (September 2022) - DiGiacomo, Michelle; Prichard, Ros; Allida, Sabine; Delbaere, Kim; Omari, Abdullah; Inglis, Sally C
Objectives: To ascertain a comprehensive perspective of the impact of peripheral arterial disease (PAD) on people including needs for access to disease specific information, education, services, and support. Methods: Participants were recruited from outpatient clinics at a tertiary hospital in metropolitan Australia. Telephone and face-to-face semi-structured interviews were conducted with nine individuals living with PAD and analysed using qualitative content thematic analysis. Results: The nine participants were on average 74.2 (SD 10.9) years and predominantly women (67%). Lack of understanding of PAD and inconsistent information resulted in confusion regarding self-management strategies. Effects of pain and mobility problems were amplified for participants who lived alone and did not have an informal carer. Discussion: Poor quality of life in PAD reflects pain, social isolation and fear of falls. Multidisciplinary teams with case managers should consider older people's living situations and needs for additional support services and education to facilitate integrated care.